2023
DOI: 10.1177/10732748231168318
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Breast Cancer Patients: A Systematic Review of the Qualitative Studies

Abstract: Objective Quality of life (QoL) in breast cancer patients is still an important topic. Despite numerous quantitative scales, qualitative studies can help to in-depth understand the QoL of breast cancer patients. The purpose of this systematic review was to integrate qualitative studies on the QoL of women with breast cancer. Methods A literature search was performed in electronic databases including PubMed, Scopus, and Web of Science from January 1, 2010 until June 28, 2022 to find out qualitative studies asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…However, even in the presence of pain and severe side effects, the idea of moving on was discursively embraced by the women. Similar ndings were reported by Heidary et al [23] The authors found that survivors expressed distress about their capability to return to normal life despite being declared cancerfree. This could be because of what they may have passed through, seen or read about cancer that have consciously altered their worldview about the whole survivorship story.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, even in the presence of pain and severe side effects, the idea of moving on was discursively embraced by the women. Similar ndings were reported by Heidary et al [23] The authors found that survivors expressed distress about their capability to return to normal life despite being declared cancerfree. This could be because of what they may have passed through, seen or read about cancer that have consciously altered their worldview about the whole survivorship story.…”
Section: Discussionsupporting
confidence: 88%
“…The authors reiterated the need to develop cultural survivorship programs that will capture emotional information, provide in-kind support, and empower these patients for life adjustment. Heidary et al [23] added that self-nurturance helps the survivors to have new concept formation about self and health. Most participants demonstrated self-nurturance, which fosters both the physical and psychological health requisite to their happiness, well-being and self-growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family support can enhance the breast cancer patients life quality, as it is crucial for every patient (Heidary et al, 2023;Nurhidayati et al, 2023;Tan et al, 2023). Families play a significant role in providing motivation, attention, and care, addressing the needs of patients undergoing treatment (Karam et al, 2021;Novitarum et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported stressor was a higher level of concern regarding the experienced anxiety and depressive symptoms and a higher fear of cancer recurrence (Massicotte et al, 2021). The previous review studies have only evaluated the quality of life in general, not specific to physical and mental HRQoL, and not during the COVID-19 pandemic (Heidary et al, 2023;Mokhtari-Hessari & Montazeri, 2020;Yan et al, 2016). Thus, this original study aimed to investigate the determinants and analyze their correlation to physical and mental HRQoL among patients with breast cancer during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%